Do the coach and athlete have the same «picture» of the situation? Distributed Situation Awareness in an elite sport context - Macquet, A.-C.; Stanton, N. A. (Applied Ergonomics, 2014)
We presented a method to assess the consistency of coach-athlete situation awareness. Results revealed similarities and important differences between the athlete and coach. Results suggest that SA information elements showed some common ground. Coaches and athletes framed information elements differently to make sense of situation.